Exploring Language Aptitude: Views from Psychology, the Language Sciences, and Cognitive Neuroscience (English Language Education,, 2018)
This book presents original, empirical data from quantitative and qualitative research studies in the field of language learning aptitude, ability, and individual differences. It does so from the perspectives of Second Language Acquisition, psychology, neuroscience and sociolinguistics. All studies included in the book use a similar and uniform layout and methodology. Each chapter contains a study examining factors such as memory, personality, self-concept, bilingualism and multilingualism, education, musicality or gender. The chapters investigate the influence of these concepts on language learning aptitude and ability. Several of these chapters analyse hypotheses which have never been tested before and therefore provide novel research results. The book contributes to the field both by verifying and contesting existent findings and by exploring novel approaches to devising research in the subject area. .